2018
DOI: 10.1080/00268976.2018.1519201
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting quadrupole relaxation enhancement peaks in proton R1-NMRD profiles in solid Bi-aryl compounds from NQR parameters

Abstract: We propose a simple method to calculate and predict quadrupole relaxation enhancement (QRE) features in the spin-lattice nuclear magnetic relaxation dispersion (R 1 -NMRD) profile of protons ( 1 H) in solids. The only requirement is the knowledge of the nuclear quadrupole resonance (NQR) parameters of the quadrupole nuclei in a molecule. These NQR parameters -the quadrupole coupling constant Q cc and the asymmetry parameter η -can be determined by NQR spectroscopy or using quantum chemistry calculations. As th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Knowledge of the finite lifetime NQR resonance lineshape, as it is presented here, might also be interesting for predicting the correct lineshape of the quadrupole resonance enhancement (QRE) effect in solids [51,52]. This issue has been addressed in [53] using only an approximated ad-hoc NQR lineshape and could be improved.…”
Section: Discussionmentioning
confidence: 98%
“…Knowledge of the finite lifetime NQR resonance lineshape, as it is presented here, might also be interesting for predicting the correct lineshape of the quadrupole resonance enhancement (QRE) effect in solids [51,52]. This issue has been addressed in [53] using only an approximated ad-hoc NQR lineshape and could be improved.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it was shown that the preparation of PPh 3 -modified graphene quantum dots gives rise to a high quantum yield and excellent stability 12 . In a wider context, the diffusivity of triphenyl compounds is also of paramount importance for medical purposes: Triphenylbismuth and triphenylantimony are currently under investigation as contrast agents for magnetic resonance imaging 13 , 14 while triphenylphosphine has recently been incorporated in a macromolecule that can be used as a vehicle for mitochondrial drug delivery 15 . Relevant mobility data, in particular in the context of graphitic materials, is also of importance as similar phosphorous-containing molecules are frequently detected in natural environments as an emerging organic pollutant 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…This limitation neglects an important source of molecular information, as the position and intensity of quadrupolar peaks provide a useful understanding of intramolecular and intermolecular interactions occurring in nitrogencontaining polymer systems. [8,11,12,20,21] Our group recently applied a different mathematical approach to include quadrupolar peaks in the NMRD profiles of Parmigiano-Reggiano (PR) cheese at three different ripening degrees. [17] This approach allowed to recognize water trapped in casein micelles, alongside water bound to polar groups in organic components, proteins and fats.…”
Section: Introductionmentioning
confidence: 99%